Cyclic-AMP-dependent proliferation of a human osteoblast cell line(HOS cells) induced by hydroxyapatite: effect of exogenous nitricoxide - Sosroseno, W.; Sugiatno, E. (Acta Biomedica Atenei Parmensis, 2008)
Background and Aims of the work: Nitric oxide (NO) has been reported to enhance the production of cAMP by hydroxyapatite (HA)-induced a human osteoblast cell line (HOS cells). The aim of the present study was to test the hypothesis that exogenous NO may up-regulate the proliferation of hydroxyapatite (HA)-induced HOS cells via the cyclic-AMP-protein kinase A (PKA) pathway. Methods: HOS cells were pre-incubated with ODQ (guanylyl cyclase inhibitor), SQ22536 (adenylyl cyclase inhibitor), forskolin (adenylyl cyclase activator), IBMX [phosphodiesterase (PDE) inhibitor], siguazodan (PDE3 inhibitor), rolipram (PDE4 inhibitor), or KT5720 (PKA inhibitor), and then, cultured on the surface of HA with or without the presence of SNAP (NO donor). The HOS cell cultures on the HA surface were added with br-cGMP (cGMP analogue), db-cAMP (cAMP analogue) with or without SNAP. The cell proliferation was assessed by a colorimetric assay. Results: The up-regulatory effect of SNAP on HA-induced HOS cell proliferation was suppressed by SQ22536 and KT5720, but enhanced by db-cAMP, IBMX, and rolipram. The HA-induced HOS cell proliferation with or without the presence of SNAP was unaltered by ODQ, br-cGMP and siguazodan. Conclusion: These results suggest, therefore, that HA-induced HOS cell proliferation may be mediated by the cAMP-PKA pathway regulated by PDE4 and that exogenous NO may amplify this cyclic nucleotide pathway, thereby augmenting HA-induced HOS cell proliferation.